Facile synthesis of electrostatically anchored Nd(OH)3 nanorods onto graphene nanosheets as a high capacitance electrode material for supercapacitors. (29th January 2018) - Arunachalam, Subasri; Kirubasankar, Balakrishnan; Murugadoss, Vignesh; Vellasamy, Devadoss; Angaiah, Subramania
Abstract : Nd(OH)3 /G hybrid is prepared by a solvothermal reduction process and used as an electrode material for asymmetric supercapacitors. Abstract : Neodymium hydroxide nanorods [Nd(OH)3 ] are developed by a facile chemical precipitation method without any surfactants/templates at ambient temperature. The neodymium hydroxide nanorods–graphene [Nd(OH)3 /G] nanohybrid is prepared by a simple solvothermal reduction process using Nd(OH)3 /GO in a mass ratio of 1 : 0.5 in dimethylformamide for 7 h. This new Nd(OH)3 /G nanohybrid can be used as an electrode material for supercapacitors; it exhibits good capacitive behaviour, with a specific capacitance of 820 F g −1 at 1 A g −1 . The nanohybrid exhibits a capacitance retention of 96% even after 3000 continuous charge–discharge cycles. This excellent electrochemical behaviour is mainly attributed to the synergetic effect of Nd(OH)3 and graphene. The asymmetric supercapacitor (ASC) device is denoted as Nd(OH)3 /G‖AC; a poly(vinylidene fluoride) electrospun membrane soaked in 6 M KOH was used as a separator as well as the electrolyte. The ASC device functions in an optimized potential window of 1.6 V with an energy density of 40 W h kg -1 . Furthermore, the ASC device exhibits excellent capacitance retention of 85.3% with a Coulombic efficiency of 97% even after 5000 cycles. This new hybrid electrode material shows impressive performance and can be used as an electrode material for asymmetric supercapacitors.